Advanced Interatrial Block Predicts New Onset Atrial Fibrillation in Patients with Severe Heart Failure and Cardiac Resynchronization Therapy. Issue 6 (2nd February 2015) - Sadiq Ali, Fariha; Enriquez, Andres; Conde, Diego; Redfearn, Damian; Michael, Kevin; Simpson, Christopher; Abdollah, Hoshiar; Bayés de Luna, Antoni; Hopman, Wilma; Baranchuk, Adrian
Abstract : Background: Advanced interatrial block (aIAB) on the surface electrocardiogram (ECG), defined as a P‐wave duration ≥120 milliseconds with biphasic (±) morphology in inferior leads, is frequently associated with atrial fibrillation (AF). The aim of this study was to determine whether preoperative aIAB could predict new‐onset AF in patients with severe congestive heart failure (CHF) requiring cardiac resynchronization therapy (CRT). Methods: Retrospective analysis of consecutive patients with CHF and no prior history of AF undergoing CRT for standard indications. A baseline 12‐lead ECG was obtained prior to device implantation and analyzed for the presence of aIAB. ECGs were scanned at 300 DPI and maximized 8×. Semiautomatic calipers were used to determine P‐wave onset and offset. The primary outcome was the occurrence of AF identified through analyses of intracardiac electrograms on routine device follow‐up. Results: Ninety‐seven patients were included (74.2% male, left atrial diameter 45.5 ± 7.8 mm, 63% ischemic). Mean P‐wave duration was 138.5 ± 18.5 milliseconds and 37 patients (38%) presented aIAB at baseline. Over a mean follow‐up of 32 ± 18 months, AF was detected in 29 patients (30%) and the incidence was greater in patients with aIAB compared to those without it (62% vs 28%; P < 0.003). aIAB remained a significant predictor of AF occurrence after multivariate analysis (OR 4.1; 95% CI, 1.6–10.7; P < 0.003). Conclusion: The presence of aIAB is an independent predictor of new‐onset AF in patients with severe CHF undergoing CRT.